The Cystine/Glutamate Antiporter, System xc–, Contributes to Cortical Infarction After Moderate but Not Severe Focal Cerebral Ischemia in Mice - He, Yan; Hewett, Sandra J. (Frontiers in Cellular Neuroscience, 2022)
Understanding the mechanisms underlying ischemic brain injury is import to the goal of devising novel therapeutics for protection and/or recovery. Previous work in our laboratory and in others has shown that activation of cystine/glutamate antiporter, system xc- (Sxc-), facilitates neuronal injury in several in vitro models of energy deprivation. However, studies on the contribution of this antiporter to ischemic brain damage in vivo are more limited. Since embolic or thrombotic transient or permanent occlusion of a cerebral blood vessel eventually leads to brain infarction in most stroke cases, we evaluated the contribution of Sxc- to cerebral ischemic damage by comparing brian infraction between mice naturally null for SLC7a11 (SLC7a11sut/sut mice). — the gene the encodes for the substrate specific light chain for system xc- − with their wild type (SLC7a11+/+) littermates following photothrombotic ischemic stroke of the middle cerebral artery (PTI) and permanent middle cerebral artery occlusion (pMCAo) rendered by cauterization. In the PTI model, we found a time-dependent reduction in cerebral blood flow that reached 50% from baseline in both genotypes 47-48 hr post-illumination. Despite this, a remarkable reduction in incidence and total infarct volume of SLC7a11sut/sut mice was revealed 48 hr following PTI as compared to SLC7a11+/+ mice. No difference in injury markers and/or infarct volume was measured between genotypes when occlusion of the MCA was permanent, however. Present data demonstrate a model-dependent differential role for Sxc- in focal cerebral ischemic damage, further highlighting that ischemic severity activates heterogeneous biochemical events that lead to damage engendered by stroke.